Tongue Schwannoma at the Median Inferior Surface in the Elderly: A Case Report - Kiho Fukushima; Kisho Ono; Kyoichi Obata; Izumi Yamamoto; Yuki Kunisada; Hirokazu Yutori; Soichiro Ibaragi (Clinical Case Reports, 2025)
ABSTRACT We report the extremely rare case of an atypical schwannoma that occurred at the median inferior surface of the tongue in an elderly patient. We performed an excisional biopsy to achieve a definitive diagnosis. Based on the histopathological findings, we diagnosed a schwannoma (mixed type, Antoni A/B).